Analisis Work-Life Balance Terhadap Kepuasan Kerja Pada Pekerja Generasi Milenial - Devina Damayanti; Enjang Suherman (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to analyze the impact of work-life balance on job satisfaction among millennial workers. The research method used is descriptive qualitative. The data sources for this study include primary data obtained from researcher observations and in-depth interviews, as well as secondary data from journals, books, and other relevant materials related to the research topic. The results of the study indicate that work-life balance significantly affects job satisfaction among millennials, with an impact rate of 40%.